The educational effects of 19th century disentailment of catholic church land in Colombia (2008)
The aim of this paper is to analyze the effects of land concentration prompted by the distribution of disentailed Church land during the second half of the 19th century on the accumulation of human capital, in early 20th century Colombia. Utilizing existing primary sources on the process of land disentailment and the 1912 National Census, descriptive statistics and econometric evidence show a significant and negative relationship between the amount of disentailed land during the 1870s at municipal level with literacy and school enrollment rates of males in 1912.